Facilitating Students’ Creativity, Innovation, and Entrepreneurship in a Telecollaborative Project - Shadiev, Rustam; Yi, Suping; Dang, Chuanwen; Sintawati, Wayan (Frontiers in Psychology, 2022)
In this study, telecollaborative learning activities were carried out in virtual learning environments created by the 360-degree video technology. We aimed to facilitate students’ creativity, innovation and entrepreneurship. Two groups of students, a group of junior high school students from China (n=15) and a group of university students from Indonesia (n=10), participated in the study. Students created cultural learning content using the 360-degree video technology which considered to be creative, innovative and entrepreneurial, shared it with their international partners on the telecollaborative platform and then watched content of their partners to experience virtual panoramic tours. After that, students exchanged their ideas and comments with each other in order to improve content quality. We investigated whether participation in telecollaborative learning activities positively impacts students’ creativity, innovation, and entrepreneurship. The data was collected through questionnaires and interviews. We also analyzed content created by the participants in learning activities. Two main findings were obtained: (1) technology-supported learning activities improved participants’ creativity, innovation and entrepreneurship, and (2) the participants positively perceived their learning experiences. Based on our results, we proposed several suggestions and derived some implications.